Longitudinal Effects of School-Based Physical Activity on BMI, Motor Skill Development, and Sleep Quality in Elementary School Children - Annemarie Christ; Krysten Rocha; Angela Saccà; Khairul Zikri (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2026)
The purpose of the study. Childhood obesity and physical inactivity represent significant public health challenges affecting multiple dimensions of child health and development, including body mass index (BMI), motor competence, and sleep quality. This longitudinal study examined the effects of a 12-week school-based physical activity (PA) intervention on BMI, motor skill development, and sleep quality in elementary school children, with a one-year follow-up assessment. Materials and methods. A controlled longitudinal design was employed with 143 elementary school children (grades 4–5; M = 10.3 years; SD = 0.8; 48% female) recruited from 6 primary schools. The intervention group (n = 73) participated in an enhanced PA program (additional 120 minutes per week of structured physical activity) for 12 weeks, while the control group (n = 70) maintained regular school curriculum. BMI, motor skill performance (50-meter run, jump rope, sit-and-reach, 1-minute sit-ups), moderate-to-vigorous physical activity (MVPA), and sleep quality (Pittsburgh Sleep Quality Index for children) were assessed at baseline, 12 weeks, and 12 months post-intervention. Results. Repeated-measures ANOVA revealed statistically significant group × time interactions for BMI (F(2, 141) = 18.44, p < 0.001, η² = 0.21), motor skill performance (F(2, 141) = 22.67, p < 0.001, η² = 0.24), and sleep quality (F(2, 141) = 15.32, p < 0.001, η² = 0.18). The intervention group demonstrated a significant BMI reduction (−0.8 kg/m²; p < 0.001), improved motor skills (+19% on composite score; p < 0.001), increased MVPA (+41 minutes/day; p < 0.001), and enhanced sleep quality (+1.8 hours; p = 0.002). Benefits persisted at 12-month follow-up with partial effect maintenance. Conclusions. School-based physical activity interventions of 120 minutes weekly demonstrate significant and sustained positive effects on BMI, motor skill development, and sleep quality in elementary school children. These findings support the implementation of integrated PA programs as an evidence-based strategy for comprehensive child health promotion and obesity prevention.